PERSPECTIVE ON HEALTH SEEKING BEHAVIOR OF PATIENTS WITH OROPHARYNGEAL CANCERS FROM A PAKISTANI BACKGROUND - Shoaib, Maria; Ahmed, Syed Ahsanuddin; Waqar, Syed Muhammad; Abbasi, Zainab; Yusuf, Farah Hafiz (Journal of Ayub Medical College Abbottabad, 2016)
Oropharyngeal cancers are the most common cancers of head neck region, they are placed amongst the top ten malignancies globally and around 40% of all the cancers in South and South East Asia. Patient’s personal behaviour impacts causality more than the environmental factors in the pathology and prognosis of this particular cancer. In our country risk factors are based on poor infrastructure of the health care system, illiteracy, poor socioeconomic status, Betel nut and quid, smokeless and smoke tobacco. We recommend that an active precautionary approach is required to restrict the rising incidence in the oral cancers, particularly due to culturally related risk habits and reluctance to seek early healthcare amongst our people. Primary prevention is the need of time. Keywords: Oro Pharyngeal Cancers; Pakistani Population; Personal Reluctance; Cultural Risk Factors; Primary Prevention